Horizontal ecological compensation mechanism and technological progress: theory and empirical study of Xin'an River Ecological Compensation Gambling Agreement. Issue 3 (23rd February 2023) - Wang, Haisen; Yang, Gangqiang; Ouyang, Xiao; Tand, Ziyi; Long, Xiaofeng; Yue, Ziyang
Abstract : The Xin'an River ecological compensation mechanism is China's first horizontal compensation mechanism to improve the ecological environment of the downstream areas and increase the fiscal revenues of the upstream areas. Although the amount invested in the program is increasing every year, few studies have been conducted to evaluate the impact of the program. Based on the Levinsohn–Petrin method and a comprehensive dataset of Chinese industrial companies from 2009 to 2015, we employed the k-nearest neighbor propensity score matching–difference-in-difference (PSM-DID) to explore the impact of the Xin'an River Ecological Compensation Gambling Agreement (ECGA) on company technological progress and its drive mechanism. The empirical results show that ECGA inhibits the technological progress of upstream industrial companies and has more pronounced inhibitory effects for heavy-polluting companies. ECGA indirectly inhibits the technological progress in upstream companies by affecting profitability, scale, human capital, foreign direct investment, and management efficiency.